(untitled) (Politeja, 2025)
Devolution in the UK is rightly described as one of the most important constitutional reforms since the turn of the 21st century. After 25 years of implementation, there is now good reason to ask about the outcome of this reform. The aim of this presentation is to examine the advantages and disadvantages of this process in the context of a meta-governance approach. To do this, the author (1) presents the theoretical underpinning of a meta-governance approach; (2) checks the process of implementation reform; (3) follows the evolution of devolved governments and, finally, (4) analyses the current state of debate about the future of devolution. The research methodology is based on comparative studies, desk research and content analysis of the interviews with ministers from the regional governments conducted by the Institute for Government. In conclusion, it is said that devolution reform slowly but consequently changed the political and administrative structure of the UK, however, it has not resolved the problem of the fact that the UK remains the most centralized country in Europe in terms of local and regional governance as well as continuous tensions within intergovernmental relations.